Influence of organic nutrient management practices for noni (Morinda citrifolia) when grown as an intercrop in coconut garden - MAHESWARAPPA, H P; SUBRAMANIAN, P; KUMARI, A GEETHA (The Indian Journal of Agricultural Sciences, 2017)
The experiment was conducted to study the performance of noni (Morinda citrifolia) as an intercrop in coconut garden under organic nutrient management at ICAR-Central Plantation Crops Research Institute, Kasaragod, Kerala, during 2012-2015. Four organic source of nutrient management treatments, viz. T1: Vermicompost (VC) alone, T2:Vermicompost+vermiwash (VW)+ biofertilizers (BF), T3: VC+VW+BF+coir pith application and T4: VC+VW+BF+ in situ green manuring+ husk incorporation (At the time of planting and once in two years in between rows) + coconut leaf mulch were replicated five times in RBD design. Vermicompost, vermiwash (1:10 dilution) and biofertilizers (Azospirillum and Phosphobacteria) were applied at 6, 12, 18 months after planting (MAP) @ 2 kg, 2 l/plant, and 25 g/plant, respectively and at 24 MAP @ 5 kg 4 l/plant, and 50 g/plant, respectively. Among the treatments, VC+VW+BF+In situ green manuring + husk incorporation + coconut leaf mulch resulted in significantly greater noni fruit yield (6159 kg/ha/year) and the maximum net return (Rupees 108 695/ha) and B:C ratio (1.31) compared to other treatments.